Histopathological Pattern of Glomerulonephritis: Experience from BIRDEM General Hospital, Dhaka, Bangladesh (BIRDEM Medical Journal, 2017)
Background: Glomerulonephritis (GN) remains the most probable underlying cause of end stage renal disease of uncertain aetiology in many developing countries including Bangladesh. The pattern of glomerular disease varies widely from country to country. In Bangladesh, the incidence and histological pattern of GN is inadequately described. We performed a study, aiming to determine the pattern of GN in a diabetic hospital of our country.Methods: It was a cross-sectional hospital based prospective study conducted at BIRDEM General Hospital starting from July 2013 to December 2014. It included all patients with suspected GN who underwent native kidney biopsy.Results: Total 57 biopsies were performed and four cases other than primary or secondary GN (renal cortical necrosis 1, tubulointertsitial nephritis 2,chronic GN 1) were excluded i.e total number of PGN was 37 and secondary GN was 16. number of patients with were 53. M:F was 1.2:1.Mean age was 42.35±15(14-72) years. Thirty one (58.49%) of the study subjects had diabetes mellitus (DM). Mesangialproliferative GN (15/37,40.5%) and diabetic nephropathy (9/16,56%) were the commonest histopathological pattern found among primary and secondary GN respectively. Membranoproliferative GN (10/37,27%),was the second commonly observed pattern followed by focal segmental proliferative GN (8%), membranous nephropathy (8%), focal segmental glomerulosclerosis (5.4%) in primary GN and lupus nephritis (6/16,38%) and Wegeners granulomatosis (1/16) were other varieties in secondary group. Among 53 cases, 37 had proliferative variety. Nephrotic range proteinuria (41.5%) was the commonest indication of biopsy and 22% had post biopsy bleeding and 3.7% required blood transfusion.Conclusion: In conclusion, mesangial proliferative and membranoproliferative GN are the two common causes of primary GN. Diabetic nephropathy is the commonest cause of secondary GN. Nephrotic range proteinuria was the main indication of biopsy. Post biopsy complication was negligible. Creation of a national renal registry is essential for obtaining more specific epidemiological data.Birdem Med J 2016; 6(2): 67-73